Colorado future of gas: building decarbonization literature review - Eisenbeis, Ellen D., author; Evans, Alexandra I., author; Hoffer, Katherine A. Heriot, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2023)
Requested by the Colorado Future of Gas Steering Committee, this literature review examines a wide range of research on building emissions reductions. Under Colorado's Clean Heat Standard (Senate Bill 21-264), gas utilities will be required to develop clean heat plans that meet the state's goal of reducing greenhouse gas (GHG) emissions by 4% below 2015 levels by 2025, and 22% below 2015 levels by 2030. This literature review examines different emissions reduction strategies and provides an overview of the costs and emissions impacts associated with the eligible resources allowed under the Clean Heat Standard. The review also discusses how emissions reduction strategies could impact customers, disproportionately impacted communities, the workforce, existing infrastructure, and reliability.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- Colorado; Greenhouse gas mitigation -- Colorado